Augmentation of the insufficient tissue bed for surgical repair of hypospadias using acellular matrix grafts: A proof of concept study. (April 2021) - Morgante, Debora; Radford, Anna; Abbas, Syed K; Ingham, Eileen; Subramaniam, Ramnath; Southgate, Jennifer
Acellular matrices produced by tissue decellularisation are reported to have tissue integrative properties. We examined the potential for incorporating acellular matrix grafts during procedures where there is an inadequate natural tissue bed to support an enduring surgical repair. Hypospadias is a common congenital defect requiring surgery, but associated with long-term complications due to deficiencies in the quality and quantity of the host tissue bed at the repair site. Biomaterials were implanted as single on-lay grafts in a peri-urethral position in male pigs. Two acellular tissue matrices were compared: full-thickness porcine acellular bladder matrix (PABM) and commercially-sourced cross-linked acellular matrix from porcine dermis (Permacol™). Anatomical and immunohistological outcomes were assessed 3 months post-surgery. There were no complications and surgical sites underwent full cosmetic repair. PABM grafts were fully incorporated, whilst Permacol™ grafts remained palpable. Immunohistochemical analysis indicated a non-inflammatory, remodelling-type response to both biomaterials. PABM implants showed extensive stromal cell infiltration and neovascularisation, with a significantly higher density of cells ( p  < 0.001) than Permacol™, which showed poor cellularisation and partial encapsulation. This study supports the anti-inflammatory and tissue-integrative nature of non-crosslinked acellular matrices and provides proof-of-principle for incorporating acellular matrices during surgical procedures, such as in primary complex hypospadias repair.